An Analysis of Psychology Characters in Novel “BUKAN PELAJAR BIASA” by Shandy Tan - Sabaswaly, Diana Reby; Momo, Lidia Lali (Journal of Language, Literature and Teaching, 2024)
This research aims to describe the psychology of the characters in the novel "Not an Ordinary Student" by Shandy Tan. With a literary psychology approach. The method used is a qualitative descriptive method, namely analyzing descriptive data by presenting and describing something that exists.The data source was obtained from the library, namely the novel "Not an Ordinary Student" published by PT Elex Media Komputindo Gramedia Group, IKAPI Member, Jakarta 2010. Data analysis techniques were carried out by: 1. Classifying the data that has been collected, 2. Re-examine the data that has been classified, 3. Analyze the data that has been classified according to the problem from the novel "Not an Ordinary Student" 4. Conclude.Based on the results of the analysis above, it can be concluded that in the novel "Not an Ordinary Student" by Shandy Tan there are 5 characters, namely: Imelda, Ibu, Erik, Uncle Dennis, and Aunt Anna who have different personalities from one character to another.